Characteristics of Groundwater from Fractured Hardrocks in West Coast of Peninsular Malaysia - Raja Azie, Raja Zainariah (1997)
The thesis examines on the chemical characteristics of groundwater found in granitic and metasedimentary rocks of the West Coast of Peninsular Malaysia. A total of 133 tubewells having diameter 20 cm were studied. The wells were drilled to a depth between 100 to 200 m. The top 20 to 40 m of the wells were cased, fol lowed by 60 to 80 m Of slotted casing. The remaining depth of the wells was left open. The present study shows that the quality is mostly fresh with average pH and conductivity around 6.5 and 200 µS/cm respectively. The total dissolved solids range between less than 100 mg/l to more than 200 mg/l with average of a bout 120 mg/l. The groundwater is classified as soft to hard water because the hardness ranges between 12 mg/l to 180 mg/l. the groundwater facies was found to be Calcium Bicarbonate, Magnesium Bicarbonate and Sodium B icarbonate water. Calcium and Magnesium in metasedimentary water have average of about 17 mg/l and 21 mg/l, respectively. For granite, the average of Ca and Mg is 8.75 mg/l and 2.85 mg/l. The amount of iron content can be as high as 15 mg/l with average of 1.5 mg/l. More than 50% of the groundwater samples exceeds the limit of iron for drinking water of 0.3 mg/l. Fluoride concentration is generally low with average Of 1.0 mg/l. However, groundwater from granite can reach the level of Fluoride to 11.5 mg/l. the groundwater is classified as medium to low salinity hazard and low in sodium; therefore it is suitable for irrigation. The thesis also examined the production capability of the hardrock aquifers. The top 20 m was mainly in the residual soil and weathered part of the rock. Fresh hardrocks were normally encountered at depth more than 40 m. the static water level or water table in the study area were found to be less than 20 m deep. Four of the wells were outflowing automatically above the well head casings, which was constructed about 0.5 m above ground. High discharge rates up to 800 m³/well/day were encountered from wells that penetrated major fracture zones. Average discharge rate for metasedimentary and granite aquifers were 400 m³/well/day and 300 m³/well/day, respectively and the drawdown is generally less than 50 m from the ground level. The wells were drilled for various purposes such as for rubber, latex, textiles and mineral water bottling factories, poultry and agricultural activities and domestic water supply.